Rethinking education for a global, transcultural world - Soriano, Encarnación (Research in social education., 2015)
The global networking promoted by technology, globalization and migration that are occurring at a large scale, requires school systems that develop in the students new types of skills, based on the ability to understand the world and its problems and instill a sense of responsibility and cooperation to enhance the resolution of the great problems of mankind.Rethinking education is essential in a global, transcultural, changing and communicated world. Throughout the book Rethinking Education for a Global, Transcultural World is argued and analyzed how to build relationships between the school and society, and the possibilities of transcending the barriers in different national contexts: Chile, Israel, Mexico, Morocco, Poland, and Spain.The main goal we want to achieve with the contributions made in the book is to know how education systems and schools in different countries respond to the social changes caused by globalization, migration and new communication technologies.The authors are professors of different scientific disciplines and different faiths, cultures and points of view, living the realities described in the chapters and thinking from these realities how to improve and how should be the education in a global, challenging and ever-changing world. We stress the importance of this book and its implications in the education of children and youth and in the preparation of teachers. For this reason, this is a book designed for teachers of primary and secondary schools, parents, principals, supervisors, university teachers who prepare school teachers, university students and those who want to know and think about education in a global and intercultural world and new forms of communication to face learning, whether at local or at world level.The mission of all is continue building education, and to facilitate this work in this book are presented contributions and recommendations of professionals around the world that will allow the reader to know, analyze, understand and appreciate the importance of education to prepare students to function with open and critical thinking in a global world. The chapters do not offer a panacea, but offer many ideas on how, through education, prepare citizens for a global and transcultural society.